Birch, Chris (London, 2011)
2011 "Birch, Chris", 2011, HistoryTalk Chris studied at Bristol University. After graduating, he became a Medical Representative from 1951- 1955, selling drugs to GPs, chemists and pharmacists in London. He left this job to go to Warsaw for the 1955 World Federation of Democratic Youth. On returning to Britain he worked as an sub- editor at the Iron & Steel Institute and later became editor of Municipal Engineering. From 1981, he was a freelance journalist and became involved, in 1986, with work around HIV/ AIDS.